An Overview of Exosomes in Cancer Therapy: A Small Solution to a Big Problem - Rodrigues, Paulo (2020)
Exosomes are defined as a type of extracellular vesicle released when multivesicular bodies of the endocytic pathway fuse with the plasma membrane. They are characterized by their role in extracellular communication, partly due to their composition, and present the ability to recognize and interact with cells from the immune system, enabling an immune response. Their targeting capability and nanosized dimensions make them great candidates for cancer therapy. As chemotherapy is associated with cytotoxicity and multiple drug resistance, the use of exosomes targeting capabilities, able to deliver anticancer drugs specifically to cancer cells, is a great approach to overcome these disadvantages. The objective is to assess treatment e ciency in reducing tumor cells, as well as overall safety and response by cancer carriers. So far, results show exosomes as a promising therapeutic strategy in the fight against cancer. This review summarizes the characteristics and composition of exosomes, as well as explaining in detail the involved parties in the origin of exosomes. Furthermore, some considerations about exosome application in immunotherapy are addressed. The main isolation and loading methods are described to give an insight into how exosomes can be obtained and manipulated. Finally, some therapeutic applications of exosomes in cancer therapy are described.